Effects of human resource management (HRM) practices on project performance in construction industry - Lee, Wai Yee (2015)
This thesis explained about Human Resource Management (HRM) practices used by the construction companies and the effects of HRM practices on project performance. Human Resource Management (HRM) is known as system of activities and strategies to coordinate and manage human capitals in company in order to achieve organizational goals. Many construction projects are mostly complex and difficult to manage and HRM practices are mostly used in company for effective functioning and it has the potential to influence the success or failure of projects. In construction industry, there are many human resource issues lead to poor project performance such as are poor project work design and structure, shortage of qualified skilled employees, changing workforce demography, a high rate of employee turnover and high rate of burnout. This research was conducted to identify the common HRM practices used by the construction companies and to determine the effects of HRM practices on project performance. Data was collected through distributing questionnaire by email and was analyzed using SPSS 2.0 software. Descriptive analysis was used to identify the common HRM practices used by the construction companies and Multiple Regression analysis was used to determine the effects of HRM practices on project performance. From the findings, Human Resource Management (HRM) practices have positive significant relationship with project performance. The results of research can provide proof and insights and to encourage construction firms implement effective HRM practices to improve project performance in future.